Rancang Bangun Tongkat Khusus Tunanetra Dengan Menggunakan Bahasa C Berbasis Arduino Mikrokontroller - Muhammad Faishal Ginarso; Riswal Hanafi Siregar (CV. Multi Kreasi Media, 2022)
Blindness is a condition in which someone has a disturbance in their sense of sight. The only assistive device currently used for blind people is a cane. However, sticks are considered less effective because the reach of the sticks is not too wide and long, and less efficient when used in the middle of a crowd of people around them. On the basis of these problems, this research was conducted to help blind people to be aware of the obstacles that exist around them. With this background, the authors try to design a tool that can make it easier for blind people to navigate while doing their activities. The tool to be designed is a visual aid using a microcontroller-based ultrasonic sensor. Arduino UNO is used as the brain of the blind assistance program which acts as a microcontroller and the ultrasonic sensor controller will produce sound through the headset.